PENGARUH PEMBIAYAAN MUDHARABAH DAN MUSYARAKAH TERHADAP PROFITABILITAS PADA BANK SYARIAH BRI (2012-2019) - Mega Lusyana; Wirman (Prodi Ekonomi Syariah Universitas Majalengka, 2021)
Syariah banking has experienced a fairly rapid and widespread development in Indonesia. Syariah banking is currently experiencing very significant progress, the occurrence of the global financial crisis on the one hand has made Islamic banking develop rapidly. This study aims to examine the effect of mudharabah and musyarakah financing on profitability at BRI Syariah Bank (2012-2019). Sources of data in this study are secondary data in the form of financial reports on the Bank BRI Syariah website www.brisyariah.co.id. The method used in this research is quantitative with descriptive research type. The data analysis technique used in this study is multiple linear regression analysis. In mudharabah financing, capital is provided by the bank as the owner of the funds to facilitate capital for customers as managers in running a business. The results showed that the funding of mudharabah and musyarakah results had a significant effect on profitability (ROA). This influence can be seen from the amount of mudharabah and musyarakah funds distributed by Islamic Commercial Banks. Testing and data analysis found that mudharabah and musyarakah had a significant effect on profitability. Profit sharing financing for mudharabah and musyarakah has a positive and significant effect on profitability at BRI Syariah banks. This shows that an increase in mudharabah and musyarakah financing can increase the profitability of BRI Syariah Bank.